Correction: Association of excessive screen time exposure with ocular changes leading to astigmatism in children - Shah, Mutahir; Natarajan, Satheesh Babu; Ahmad, Nafees (PloS one, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0317961.].